Batang Ina Family Communication Patterns and Teenage Pregnancies among Filipino Youth - Vilma Mae Ventanilla; Ventanilla, Jean Pauline Villaruel (Asean Social Work Journal, 2022)
Teenage pregnancy is one of the most pressing issues in our society today, especially among Filipino women. The purpose of this research study is to describe the patterns and relationships between family communication and the chances of teenage pregnancy among young Filipino women. Parents play a crucial part in the growth and development of their children hence, they also influence the sexual behavior of adolescents. However, conservatism in Filipino families, rooted in religious beliefs, affects the information process of sex. Through the case study conducted using a phenomenological approach among six teenage mothers, the researchers presented the experiences and stories of teenage pregnancy of selected teenage mothers. From this, the researchers identified the common themes among Filipino families, and their implications on teenage pregnancy. Drawing from the Family Communication Pattern Theory, this research study explores how lack of parental communication within the family affects the chances of teenage pregnancy among Filipino youth. By capturing the experiences and perspectives of teenage mothers living in Region IV-A, the researchers present an informed understanding of the previously scrutinized analyses on the causes and effects of teenage pregnancy.